The impact of television openness on the spread of cultural alienation among the youth of the Kurdistan Region (a field study) - حسن, هيمن مجيد (Sulaimani Journal for Humanities, 2019)
This study deals with the subject of the openness of television in relation to cultural alienation, which is considered by most of those who are interested in it from the biggest challenges facing the countries and entities underdeveloped and young citizens in particular, including the Kurdistan region. Where there are two options, not more, either to build a nation with a commitment to the rights of citizenship and structural social justice, or continue to identify with the problems of alienation and its various destructive consequences, which became a realistic threat to its future on this planet. Social entities are not constitutive institutions, constitutions, laws, and armies; they are community-based projects that are functional and interactive with their active human forces, who feel their human existence, which is a true indicator of their vitality. This is what we will try to understand in our research, which revolves around the impact of television openness on the spread of cultural alienation of young people of Kurdistan. Finally, this research relied on university students for their field mobility because they are most appropriate in expressing opinions about such phenomena and their implications for their individuality in terms of their cognitive, age, behavioral, emotional and other structural variables, as well as their representation of most segments, In the region.